Social and environmental conflicts due to the water of the submissional and lower São Francisco rivers (Research, Society and Development, 2023)
The occurrence of conflicts is established within the frustration of expectations around order and norms, the legal system being an equalizer in the balance and construction of principles of conduct. The objective of this study was to analyze the occurrence of conflicts over water use in the Submédio and Lower São Francisco region, associated with changes in water quality and dynamics of land use and land cover. Using Edgar Morin's complex method, based on Luhmann's rationale, to present data on institutionalized conflicts in Brazil between 2016 and 2020. The results indicate that the main changes that resulted in conflicts are associated with dams and changes in flow, vegetation suppression, sedimentological changes, direct damage to water quality and restrictions on access to water resources. The decisions and arguments of the main social actors involved, on the other hand, are based around the legal foundations that govern the activities, in some cases, assuming risks of frustration. It is concluded that there is a demand for grouping and integrating data to assist in the practice of law, especially considering that the hydrographic basin analyzed is federal and requires transdisciplinary investigation of the phenomena.